Off-season leafy coriander production technology under shade net covered tunnels - Singh, Ravindra; Choudhary, Sharda (Indian Farming, 2020)
Leafy coriander production during off-season can be a boon for the poor and marginal farmers ofthe arid and semi-arid regions in the urban and peri-urban areas. Off-season leafy corianderproduction technology under shade net cover tunnels developed at ICAR-National ResearchCentre on Seed Spices reveals that 50% black and 90% green shade net covered tunnels gave162.8 and 167.2 kg/100 m2 coriander leaf yields with net returns of ` 9,817 and ` 9,693 during2015, whereas during 2016 the yield levels were 101.4 and 106.0 kg/100 m2 with net returns of` 7,921 and ` 7,984 respectively. In the field demonstration at farmer’s field, the technology isproven to yield higher returns and double income in comparison to open conditions.